The Importance of Shop Signboards in the Chinatown Area of Suryakencana Street, Bogor - Soegih Poerawidjaya; Tri Wahyu Retno Ningsih; Ayesa Ayesa (Institut Agama Islam Negeri Palopo, 2023)
Chinatown is a term for a district in a city inhabited by Chinese ethnic. Most Chinese ethnicities that live in Chinatown on Suryakencana Street, Bogor City, have a livelihood as merchants and store owners. Store name board is one of the important elements of stores then be regulated by the government and inflicts the reduced value of Chinatown. This research aims to know the important values of store name boards as the identity of Chinese ethnic on Suryakencana Street, Bogor City. This research uses qualitative descriptive methods such as interviews and literature reviews. This research result shows that the laws in effect from 1966 to 2000 discriminated against Chinese ethnicities and their identities in Indonesia. That is reflected in store name boards with elements of Chinese culture such as Chinese characters (Hanzi) forced to be changed to Latin script with storeâ€™s name should have â€œIndonesianâ€ characters. After analyzing, store board names have deep means and values as the material culture of Chinese ethnic that represent important values about identity, history, and culture of Chinese which can be an added value from Chinatown on Jalan Suryakencana, Bogor City.